2005
DOI: 10.1111/j.1475-6773.2005.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Diagnoses: ICD Code Accuracy

Abstract: Objective. To examine potential sources of errors at each step of the described inpatient International Classification of Diseases (ICD) coding process. Data Sources/Study Setting. The use of disease codes from the ICD has expanded from classifying morbidity and mortality information for statistical purposes to diverse sets of applications in research, health care policy, and health care finance. By describing a brief history of ICD coding, detailing the process for assigning codes, identifying where errors ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
662
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 902 publications
(673 citation statements)
references
References 31 publications
9
662
1
1
Order By: Relevance
“…3,4 Though these codes have played a significant role in advancing research and policymaking in general, underreporting of chronic conditions with these codes is common. 3 As reported in the limitations section of our paper, we addressed this concern by requiring two ICD-9 codes for confirming the condition.…”
mentioning
confidence: 99%
“…3,4 Though these codes have played a significant role in advancing research and policymaking in general, underreporting of chronic conditions with these codes is common. 3 As reported in the limitations section of our paper, we addressed this concern by requiring two ICD-9 codes for confirming the condition.…”
mentioning
confidence: 99%
“…This would entail grouping all acute alcohol intoxication classification codes assigned by the treating physician in the back‐end of the surveillance system and excluding codes related to chronic alcohol problems. Creating a more specific sub‐syndrome risks reducing the accuracy of the grouping due to known variability in coding practices within EDs 32. Post‐hoc analysis showed promising results, with general agreement between the classification based on manual review of the triage notes and the ED diagnosis code assigned for each presentation (Table S3).…”
Section: Discussionmentioning
confidence: 95%
“…For this group, it is possible that while the triage nurse did not assess alcohol to be involved or did not document alcohol involvement, the ED clinician assessed alcohol to be a primary presenting factor and coded the presentation as such. Miscoding is also possible, with previous studies reporting the validity of coded ED data to be susceptible to the unpredictable ED environment, varying staff coding competence, unintentional and intentional misclassification and patient–clinician communication problems 15, 31, 32. This group was included in the chronic harm group as they continue to be included in the routine operation of the system, and this ensures a more conservative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been no specific reviews of ICD-9 code accuracy regarding FXS, SB, or MD in the United States, broader reviews of the literature reveal that unintentional coder errors caused by the limits of the clinician's knowledge and experience with the condition, misinterpreted information from the clinical record, and data entry mistakes lead to inaccuracy in ICD coding. [29][30][31] To control for miscoding, our inclusion criteria required two or more diagnoses of FXS, SB, or MD. The specification of at least two occurrences of a diagnosis was used in a Canadian study, which linked two surveillance systems; for spina bifida, they found an agreement rate of 64.1 %.…”
Section: Discussionmentioning
confidence: 99%